Divergent needs and the empathy gap : Exploring the experience of workplace violence against nurses employed in the Emergency Department - Koutsofta, Christina (My University, 2025)
Violence in healthcare settings, especially in emergency departments (ED), remains an important public health issue worldwide. Thus, additional insight into the effect of these incidents on nurses’ professional attitudes, their work-life and related implications to patient safety issues may be valuable. We investigated ED nurses’ living experience of exposure to workplace violence by healthcare service users, with focus on the impact on them. Following a qualitative study design, data were collected (January-June 2024) through semi-structured interviews with open-ended questions and were analyzed according to inductive, content analysis approach. Participants provided informed consent, and data collection continued until theoretical saturation was reached. The sample included six nurses. Various forms of workplace violence and its psychological, social, and professional consequences were identified. Violence was more frequently perpetrated by patients' relatives, with verbal aggression being the most common form. A fundamental divergence in needs and expectation between patients and their family members/caregivers, on one side, and participants, on the other, revealed further reflecting a pronounced empathy gap. Each group remained focused on its own priorities while struggling to recognize or accommodate others’ perspectives. This lack of mutual understanding contributed to tension that, in some cases, escalated even into physical violent incidents against the participants. A similar gap was identified between the participants’ needs and administrators’ attitudes and related policies. The failure of administrative measures to bridge this gap was described as a crucial factor in further escalating conflicts and tension in the ED. Further research on quality improvement projects including all stakeholders, aiming to enhance empathy in all parties involved, is proposed.
Keywords: violence; nurses; emergency department; implications; workplace violence; lived experience; patients; qualitative data; content analysis